Structural Plasticity and Molecular Markers in Hippocampus of Male Rats after Acute Stress. (1st July 2020) - Chen, Fenghua; Polsinelli, Benedetta; Nava, Nicoletta; Treccani, Giulia; Elfving, Betina; Müller, Heidi K.; Musazzi, Laura; Popoli, Maurizio; Nyengaard, Jens R.; Wegener, Gregers
Highlights: Acute stress significantly decreased spine number, dendritic length, and altered spine morphometric parameters. This was paralleled by changes in the gene expression of Spinophilin and Cdc42, and protein expression of homer1. Pretreatment with DMI prevented the stress-induced dendritic atrophy and spine loss 14 days after acute FS. DMI treatment without stress differentially affected the expression patterns of spine-related genes and proteins. Abstract: Stress plays a crucial role in the pathogenesis of psychiatric disorders and affects neuronal plasticity in different brain regions. We have previously found that acute foot-shock (FS) stress elicits fast and long-lasting functional and morphological remodeling of excitatory neurons in the prefrontal cortex (PFC), which were partly prevented by the pretreatment with antidepressants. Here we investigated, whether acute stress and pretreatment with desipramine (DMI) interfere in hippocampal dendritic remodeling. Male Sprague-Dawley rats were subjected to acute FS-stress, followed by measurement of time-dependent (1, 7 and 14 days) structural plasticity (dendritic arborization, spine number and morphology) in hippocampal CA1 pyramidal neurons and expression patterns of molecular markers implicated in neuronal plasticity. We found that acute stress significantly decreased spine number, dendritic length, and altered spine morphometric parameters at all time points evaluated after stress. This was paralleled by changes in the gene expression of Spinophilin and Cdc42, and protein expression of homer1. Pretreatment with DMI prevented the stress-induced dendritic atrophy and spine loss 14 days after acute FS. However, DMI treatment without stress differentially affected the expression patterns of spine-related genes and proteins. In conclusion, acute FS-stress and pretreatment with DMI significantly changed dendritic morphology, including number and morphology of spines, and the length of dendrites in hippocampal CA1 pyramidal cells as early as 1 day, and sustained up to 14 days after acute FS. The findings were paralleled by changes in gene and protein expression of actin binding and cytoskeletal proteins, Rho GTPases, and postsynaptic scaffolding proteins.